Visualizing infection of individual influenza viruses - Lakadamyali, Melike (National Academy of Sciences, 2003)
Influenza is a paradigm for understanding viral infections. As an opportunistic pathogen exploiting the cellular endocytic machinery for infection, influenza is also a valuable model system for exploring the cell's constitutive endocytic pathway. We have studied the transport, acidification, and fusion of single influenza viruses in living cells by using real-time fluorescence microscopy and have dissected individual stages of the viral entry pathway. The movement of individual viruses revealed a striking three-stage active transport process that preceded viral fusion with endosomes starting with an actin-dependent movement in the cell periphery, followed by a rapid, dynein-directed translocation to the perinuclear region, and finally an intermittent movement involving both plus- and minus-end-directed microtubule-based motilities in the perinuclear region. Surprisingly, the majority of viruses experience their initial acidification in the perinuclear region immediately following the dynein-directed rapid translocation step. This finding suggests a previously undescribed scenario of the endocytic pathway toward late endosomes: endosome maturation, including initial acidification, largely occurs in the perinuclear region.